2018
DOI: 10.1038/s42004-018-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-based rational design for boosting chiroptical responses

Abstract: Chiral molecules play indispensable roles in advanced materials and technologies. Nevertheless, no conventional, yet reliable logical strategies are available for designing chiral molecules of desired chiroptical properties. Here, we propose a general protocol for rationally aligning multiple chiral units to boost the chiroptical responses, using hexahelicene as a prototype. In this proof-of-concept study, we align two hexahelicenes in various orientations and examine by theoretical calculations to predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
191
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(215 citation statements)
references
References 60 publications
16
191
2
1
Order By: Relevance
“…It was found that, for many helicenes, the electric and magnetic transition dipole moments ( μ e and μ m , respectively) are usually not perfectly aligned in their ideal parallel or antiparallel orientation, which reduces their rotatory strength . To overcome this limitation, double helicenes with the appropriate orientation were recently introduced and were shown to display superior chiroptical properties …”
Section: Introductionsupporting
confidence: 87%
“…It was found that, for many helicenes, the electric and magnetic transition dipole moments ( μ e and μ m , respectively) are usually not perfectly aligned in their ideal parallel or antiparallel orientation, which reduces their rotatory strength . To overcome this limitation, double helicenes with the appropriate orientation were recently introduced and were shown to display superior chiroptical properties …”
Section: Introductionsupporting
confidence: 87%
“…Method of obtention To explain the enhancement of CPL in double azahelicenes, Mori et al proposed in 2018 a protocol for rationally aligning multiple chiral units to boost the chiroptical responses. 135 They used hexahelicene as a prototype; they aligned two hexahelicenes in various orientations and examined by theoretical calculations which orientation resulted in the highest chiroptical performance from either X-shaped (101, Figure 15) or S-shaped (102) double hexahelicenes. Compound 101 and 102 exhibited more than a twofold increase in intensity of circular dichroism and circularly polarized luminescence.…”
Section: Compoundmentioning
confidence: 99%
“…These diastereomers were configurationally very stable at room temperature and no racemization was observed after heating the diastereomers at 150 °C for 12 hours. Other enantioenriched derivatives bearing bromo (135) and carboxaldehyde (136) Bedekar et al reported the synthesis of aza [7]helicene in 2014, 168 and aza [9]helicene in 2016, 169 bearing a central N-butyl-carbazole unit (Scheme 35). Upon classical oxidative photocyclization process, the "angular-angular" compound 139a was obtained together with other isomeric structures named "angular-linear" 139b, 'linear-linear" 139c and "linear-fused-angular" 139d.…”
Section: Carbazoles From Oxidative Photocyclizationmentioning
confidence: 99%
“…Planar and helical chiralities, as found in helicenes, were highlighted to promote important dissymmetry factors because of the larger magnetic transition dipole moments induced by aromatic distortion. Hence, important efforts were made to rationalize this observation with the calculation of and and the determination of the θ angle (Sato et al, 2017 ; Ito et al, 2018 ; Tanaka et al, 2018b , c ). The outstanding | g lum | value of 0.152 reported for the single-wall carbon nanotubes (Dhbaibi et al, 2019 ) cyclo-2,8-chrysenylene by Isobe and Sato was attributed to the unusually important magnetic transition dipole moment originating from a cyclic aromatic structure which allows and facilitates a magnetic field-induced current loop (Sato et al, 2017 ).…”
Section: Physical Basis Of Cpl and Strategies To Achieve Strong Cpl Ementioning
confidence: 99%